A FAHP AND VIKOR METHOD FOR EVALUATION OF THE FINANCIAL PERFORMANCE OF AGRICULTURE COMPANIES LISTED ON THE BELGRADE STOCK EXCHANGE - Milorad Kovjanić; Predrag Vukadinović; Snežana Knežević; Tijana Obradović; Aleksandra Mitrović; Aleksandar Grgur; Marko Milašinović (Ekonomika Poljoprivrede (1979), 2023)
Decision-making can be improved by using different models by financial statements users for different purposes. In this paper, the FAHP model was implemented for financial performance evaluation of companies operating within the A-agriculture, forestry and fisheries sectors on the Belgrade Stock Exchange. In addition, we used the VIKOR method, for ranking companies against the results achieved. With all the constrains shown, the research presented in this paper, raises questions for insight and future development, through the possibilities of ranking the financial performance of the company.